Random measurement and prediction errors limit the practical relevance of two velocity sensors to estimate the 1RM back squat - Warneke, Konstantin; Skratek, Josua; Wagner, Carl-Maximilian; Wirth, Klaus; Keiner, Michael (Frontiers in Physiology, 2024)
While maximum strength diagnostics are applied in several sports-and rehabilitative settings, the dynamic strength capacity was determined via the one repetition maximum (1RM) testing for decades. Since literature concerned several limitations, such as injury risk and limited practical applicability in large populations (e.g. athletic training groups), the strength prediction via the velocity profile received growing attention within the last years. Referring to relative reliability coefficients and inappropriate interpretation of agreement statistics several, previous recommendations neglected the systematic and random measurement bias. Consequently, this paper explored the random measurement error arising from repeated testing (repeatability) and the agreement between two common sensors (vMaxPro and TENDO) within one repetition, using minimal velocity thresholds as well as the velocity=0m/s method. Furthermore, agreement analyses were applied for the estimated and the measured 1RM in 25 young elite male soccer athletes. Results reported repeatability values with ICC=0.66-0.80, which was accompanied by and mean absolute (percentage) error (MAE,MAPE) of up to 0.04 -0.22m/s and ≤7.5%. Agreement between the two sensors within one repetition showed a systematic lower velocity for the vMaxPro device compared to the TENDO, with ICCs ranging from 0.28-0.88, which were accompanied by an MAE/MAPE of ≤0.13m/s; 11%. Almost all estimations systematically over/underestimated the measured 1RM, with a random scattering between 4.12 -71.6%, dependent on the used velocity threshold. In agreement with most actual reviews, the presented results call for caution when using velocity profiles to estimate strength. Further approaches must be explored to minimize especially the random scattering.